Housing logic: Rationalities behind housing choice behavior in coping housing market dynamics among urban residents in Sebeta Town, Ethiopia - Efa Tadesse Debele; Taye Negussie (Research in Globalization, 2022)
Urban residents do have rationalities and justifications for the housing situation they are living in. This research is aimed to address the research question that proposed why housing choice behavior is different from person to person and why residents choose the housing type that they are living in given that in the dynamic housing market there are different housing options. The researchers are dedicated to investigating housing logic that guides urban housing choice behavior as a response to housing market dynamics. Understanding the housing logic behind the housing choice behavior of urban residents in a dynamic housing market is a logical basis of this research. This study benefited from both theoretical and empirical analysis because the literature review was supported by empirical observation. To achieve the research objective, the explanatory mixed-method sequential research design was employed where quantitative data were collected from 384 respondents who were randomly selected whereas qualitative data were collected via in-depth interviews and focus group discussion. Urban residents decided to utilize housing type that fits their overall socio-economic capacity and coping abilities. Findings indicated that urban residents shifted their housing choice from formal to informal markets which imply the logic of housing choice behavior. This shifting has happened due to the lowered extent of supportiveness of formal housing market dynamics and the decline of coping abilities that was associated with the socio-economic crisis. The authors came up with the conclusion that the major housing choice logic of urban residents is affordability, accessibility, adequacy, and aptness factors. The authors would like to suggest to the municipality to strengthen the formal housing market given that the informal housing market is likely to aggravate social injustices and inequitable housing development.
Keywords: 330; Coping ability; Housing choice behavior; Housing logic; Housing market dynamics